The concept of phrasal verbs in english - Коляда, Ірина Валеріївна; Карасьова, Олена В'ячеславівна (Університет Григорія Сковороди в Переяславі, 2024)
To begin with, we are to define the concept of a phrasal verb. According to the Wikipedia, a phrasal verb consists of a main verb combined with an adverb or a preposition, or both. Usually, the meaning of phrasal verbs is not directly evident from the definitions of the individual words. Phrasal verbs are abundant in the English language, with estimates suggesting there are at least twenty-five thousand such expressions.

Для початку давайте визначимо фразове дієслово. Відповідно до Вікіпедії, фразове дієслово складається з головного дієслова в поєднанні з прислівником або прийменником, або обома. Зазвичай значення фразових дієслів безпосередньо не видно з визначень окремих слів. В англійській мові дуже багато фразових дієслів, за оцінками, існує щонайменше двадцять п’ять тисяч таких виразів.
Keywords: phrasal verbs; language; meaning; essential; example; context; use; grammar; category; фразові дієслова; мова; значення; істотне; приклад; контекст; вживання; граматика; категорія